The structural and magnetic properties of dual phase cobalt ferrite - Shyam K. Gore (Nature Portfolio, 2017)
Abstract The bismuth (Bi3+)-doped cobalt ferrite nanostructures with dual phase, i.e. cubic spinel with space group Fd3m and perovskite with space group R3c, have been successfully engineered via self-ignited sol-gel combustion route. To obtain information about the phase analysis and structural parameters, like lattice constant, Rietveld refinement process is applied. The replacement of divalent Co2+ by trivalent Bi3+ cations have been confirmed from energy dispersive analysis of the ferrite samples. The micro-structural evolution of cobalt ferrite powders at room temperature under various Bi3+ doping levels have been identified from the digital photoimages recorded using scanning electron microscopy. The hyperfine interactions, like isomer shift, quadrupole splitting and magnetic hyperfine fields, and cation distribution are confirmed from the Mossbauer spectra. Saturation magnetization is increased with Bi3+-addition up to x = 0.15 and then is decreased when x = 0.2. The coercivity is increased from 1457 to 2277 G with increasing Bi3+-doping level. The saturation magnetization, coercivity and remanent ratio for x = 0.15 sample is found to be the highest, indicating the potential of Bi3+-doping in enhancing the magnetic properties of cobalt ferrite.